J Aging Sci 2019
DOI: 10.35248/2329-884.19.07.206
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Time and Disability in Older Adults: A Systematic Review and Meta-Analysis

Abstract: This systematic review and meta-analysis examined the relationship between sedentary behavior (SB) and disability in older adults. A search was conducted using PubMed, Web of Science, and Sport Discus databases to identify eligible studies. Of the 405 studies identified, only 4 studies met our predefined criteria to be included in this metaanalysis. In these studies, participants who reported having a disability had higher levels of SB (effect size: 0.38, 95% IC: 0.14-0.62, p<0. 002) than those without disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(87 reference statements)
4
3
0
Order By: Relevance
“…Similar findings indicated that the low level of physical activity was a predisposing factor for developing a disability among individuals aged 60 years or older [23], [31]. This was supported by results of literature systematic reviews and metaanalyses that suggested the association between a sedentary life and physical disability in older adults [32]. It was difficult to made causality inferences in our study.…”
Section: Discussionsupporting
confidence: 84%
“…Similar findings indicated that the low level of physical activity was a predisposing factor for developing a disability among individuals aged 60 years or older [23], [31]. This was supported by results of literature systematic reviews and metaanalyses that suggested the association between a sedentary life and physical disability in older adults [32]. It was difficult to made causality inferences in our study.…”
Section: Discussionsupporting
confidence: 84%
“…These results are consistent with previous studies which also proved that majority of individuals with disabilities have sedentary behavior and longer sitting hours (30,31). For example, a metaanalysis published in 2019 indicated that most of the people with disabilities spent more than 5.8 h sitting during wake up time which was higher than non-disabled people (4.6 h/day) (30). A previous analysis including adults with disabilities reported that individuals with mean sitting time of more than 6 h/day had 1.55 times more hazard of mortality as compared to the ones with <4 h of sitting time (32).…”
Section: Discussionsupporting
confidence: 94%
“…Our analysis revealed that there were no significant differences in the PA status of both groups of participants whereas people with disabilities (6.1 h) had significantly longer sitting time per day as compared to the ones without disabilities (5.3 h). These results are consistent with previous studies which also proved that majority of individuals with disabilities have sedentary behavior and longer sitting hours ( 30 , 31 ). For example, a meta-analysis published in 2019 indicated that most of the people with disabilities spent more than 5.8 h sitting during wake up time which was higher than non-disabled people (4.6 h/day) ( 30 ).…”
Section: Discussionsupporting
confidence: 94%
“…However, the associations of sedentary time and patterns with functional disability remain unclear. Two recent systematic reviews of objectively measured sedentary time showed that higher levels of total sedentary time are associated with increased odds of disability [ 14 , 15 ]. However, most existing studies have been limited by cross-sectional designs [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%